Case Report: Reactivation of Chagas disease in a patient with advanced HIV 15 Years after migration - Laura O’Doherty; Annmarie White; Ali Almajrafi; Alain Fennessy; Arlene Heekin; Peter Bede; Peter Bede; Brendan Crowley; Laura Nabarro; Debbie Nolder; Claire Rogers; Catherine Moran; et al. (Frontiers in Tropical Diseases)
Chagas disease is a neglected tropical disease caused by the protozoan parasite Trypanosoma cruzi. Chagas disease reactivation is an opportunistic infection in HIV-positive patients that commonly presents as meningoencephalitis and/or central nervous system abscesses. We describe the first known Irish case of reactivation disease in a young patient from a Chagas-endemic region with previously undiagnosed HIV and profound immunocompromise. More than 15 years after migrating, he presented to the hospital with a headache, fever, and reduced consciousness. A diagnosis of Chagas disease reactivation was made with neuroimaging, epidemiological history, Chagas serology, and a brain biopsy. Despite the commencement of anti-parasitic therapy followed by anti-retroviral therapy (ART), he deteriorated and died 1 month after admission. There is no international consensus on the dosing of antiparasitic treatment or the timing of ART initiation in reactivation disease with T. cruzi in people living with HIV. This case highlights the need for further research into the management of this complex and highly morbid illness.